The impact of motivation on employee performances: a case study of plantation workers at Tabung Haji Ladang Bukit Lawiang Estate / Muhamad Alif Md Lazi - Md Lazi, Muhamad Alif (Faculty of Plantation and Agrotechnology, 2017)
High level of employee’s performance can be achieved is becoming one of the decisive factors for any organisation success. Due to this reason several factors needed to be studied and investigated. The aim of this study to identify the impact of motivation on employee performances (act as the dependent variable) of plantation workers based on the three factors are organisational culture, Training, and Financial reward. Methods for this research survey using questionnaires. Total respondent for this study are 87 respondents and was managed to be usable and valid for the further analysis of data. All the data recorded and analysed using Statistical Package for Social Science (SPSS) consist of correlation coefficient, descriptive analysis and multiple regression. The result shows that financial reward gives the higher positive impact on the employee performances, financial reward can help to improve their economic status, in addition, the basic pay rate as general workers is lower, so workers will make the financial reward as a motivation to improve their performance. Followed by training, all workers need the training to improve their performance and enhance their skills and automatically their level of performances will be increased. Lastly is organisational culture. Usually, general workers have a union to protect them, and with the union, the management will care about the welfare and build the better organisational culture. My recommendation, the management need to give their workers more opportunity to make extra work or overtime for the certain operation, in example manuring to increase their basic salary. Lastly to become more efficient and effective the estate need to improvise their technology.